A high impact resistant polyphenylsulfone composite material and preparation method thereof

The high-impact polyphenylsulfone composite material addresses the challenges of impact resistance and antibacterial properties, enhancing its applicability in medical and daily necessities.

CN118755266BActive Publication Date: 2024-12-13TAIZHOU QIXUAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411248364.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

Existing polyphenylsulfone materials lack sufficient impact resistance and antibacterial properties, limiting their application in medical and daily necessities.

Method used

A high-impact polyphenylsulfone composite material is prepared by polycondensing 4,4'-difluorodiphenylsulfone, decafluorodiphenylsulfone, biphenyl diphenol, and 2,2'-diallyl bisphenol A, and incorporating modified montmorillonite, bismercaptoborate, and pyridine Schiff base copper complex through injection molding, introducing fluorine atoms and carbon-carbon double bonds for enhanced properties.

Benefits of technology

The composite material exhibits excellent impact resistance, antibacterial properties, and self-healing capabilities, expanding its applicability in medical and daily necessities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention discloses a high-impact polyphenylsulfone composite material and a preparation method thereof, and relates to the technical field of polymer materials. When preparing the high-impact polyphenylsulfone composite material, the present invention reacts 3-mercapto-1,3-propylene glycol and 4-mercaptophenyl boric acid to obtain bis-mercapto borate; reacts 3-mercapto-1-propylamine and 2-pyridine formaldehyde and then reacts with copper acetate to obtain a pyridine Schiff base copper complex; 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenyl diphenol, 2,2'-diallyl bisphenol A are polycondensed to obtain functionalized polyphenylsulfone; nano-montmorillonite is sequentially reacted with copper nitrate and allyl triethoxysilane to obtain modified montmorillonite; functionalized polyphenylsulfone, modified montmorillonite, bis-mercapto borate, and pyridine Schiff base copper complex are mixed and then injection molded to obtain a high-impact polyphenylsulfone composite material. The high-impact polyphenylsulfone composite material prepared by the present invention has excellent self-repairing, impact resistance, antibacterial and hydrophobic properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a high-impact polyphenylsulfone composite material and a preparation method thereof. Background Art

[0002] Polyphenylsulfone, also known as polyphenylene sulfone, is one of the most widely used materials in life and production. Its main molecular chain is mainly composed of phenylene, ether and sulfone groups. These groups give it high thermal oxidation stability, melt stability and the characteristics of being usable at high temperatures. It has been widely used in safety equipment, food processing equipment, aerospace, medical and other fields. Polyphenylsulfone plays an important role in the medical field and can be used to prepare medical devices, medical consumables, dental equipment, drug delivery systems, implants in the body, etc. With the continuous improvement of people's quality of life, more and more attention is paid to health, and the demand for medical-related products is also increasing. Therefore, it is necessary to modify polyphenylsulfone, give polyphenylsulfone excellent antibacterial and impact resistance, improve the comprehensive performance of polyphenylsulfone, broaden the application scope of polyphenylsulfone in the medical field, and protect people's health, which has important practical significance and broad market prospects. Summary of the invention

[0003] The object of the present invention is to provide a high impact resistant polyphenylsulfone composite material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A high-impact polyphenylsulfone composite material, wherein the high-impact polyphenylsulfone composite material is prepared by polycondensing 4,4'-difluorodiphenylsulfone, decafluorodiphenylsulfone, biphenyl diphenol, and 2,2'-diallyl bisphenol A to obtain functionalized polyphenylsulfone; reacting nano-montmorillonite with copper nitrate and allyl triethoxysilane in sequence to obtain modified montmorillonite; and mixing the functionalized polyphenylsulfone, modified montmorillonite, bisthioborate, and pyridine Schiff base copper complex and then performing injection molding to obtain the high-impact polyphenylsulfone composite material;

[0006] The bismercapto borate is prepared by reacting 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid;

[0007] The pyridine Schiff base copper complex is prepared by reacting 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde and then reacting with copper acetate;

[0008] The decafluorodiphenyl sulfone is prepared by oxidizing pentafluorodiphenyl sulfide with potassium permanganate.

[0009] A method for preparing a high-impact polyphenylsulfone composite material, the method for preparing the high-impact polyphenylsulfone composite material comprising the following preparation steps:

[0010] (1) Add 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid in a molar ratio of 1:1 to tetrahydrofuran (10 to 12 times the mass of 3-mercapto-1,3-propanediol), add anhydrous magnesium sulfate (0.03 to 0.05 times the mass of 3-mercapto-1,3-propanediol), stir at 40 to 50°C and 300 to 500 r / min for 6 to 8 hours, and dry at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain bismercaptoborate;

[0011] (2) adding copper acetate and pyridine Schiff base ligand in a molar ratio of 1:2 to methanol with a mass 10 to 12 times that of the pyridine Schiff base ligand, stirring and refluxing at 65 to 75°C and 300 to 500 r / min for 2 to 3 hours, and drying at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain a pyridine Schiff base copper complex;

[0012] (3) 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenylene, 2,2'-diallyl bisphenol A and potassium carbonate were mixed in a molar ratio of 1:(0.7~0.9):1:(0.7~0.9):(1.1~1.2), 10~12 times the mass of cyclopentane sulfone and 5~6 times the mass of toluene 4,4'-difluorodiphenyl sulfone were added, and the mixture was stirred and refluxed at 140~150°C and 300~500r / min for 3~4h, heated to 185~195°C, and stirred for 7~8h. The mixture was cooled to room temperature, and deionized water 2~3 times the volume of cyclopentane sulfone was added. The mixture was allowed to stand for 6~8h, filtered, washed with anhydrous ethanol and deionized water for 3~5 times respectively, and dried at 50~60°C under vacuum for 8~10h to obtain functionalized polyphenylsulfone;

[0013] (4) Pre-modified montmorillonite and anhydrous ethanol were mixed evenly in a mass ratio of 1:(50-60), silane hydrolyzate in an amount of 8-10 times the mass of the pre-modified montmorillonite was added, and the mixture was stirred at 50-60°C and 300-500 r / min for 2-3 h, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 50-60°C under vacuum for 8-10 h to obtain modified montmorillonite;

[0014] (5) Functionalized polyphenylsulfone, modified montmorillonite, bis(thio)borate, and pyridine Schiff base copper complex are added into an injection molding machine at a mass ratio of 1:(0.03-0.05):(0.10-0.12):(0.10-0.12), and high impact resistant polyphenylsulfone composite materials are obtained by injection molding.

[0015] As an optimization, the preparation method of the pyridine Schiff base ligand in step (2) is: add 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde in a molar ratio of 1:1 to methanol with a mass that is 10 to 12 times that of 3-mercapto-1-propylamine, stir and reflux at 65 to 75°C and 300 to 500 r / min for 2 to 3 hours, and dry at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain the pyridine Schiff base ligand.

[0016] As an optimization, the reaction process of the pyridine Schiff base copper complex in step (2) is:

[0017] .

[0018] As an optimization, the preparation method of the decafluorodiphenyl sulfone in step (3) is as follows: under a nitrogen atmosphere, pentafluorodiphenyl sulfide, potassium permanganate and acetic acid are uniformly mixed in a mass ratio of 1:(0.4-0.6):(12-14), stirred at 10-30°C and 300-500 r / min for 10-14 min, and at 0-2°C and 300-500 r / min, a 98% aqueous sulfuric acid solution with a mass fraction of 1.5-1.6 times the mass of pentafluorodiphenyl sulfide is added dropwise at a uniform rate within 10 min, the temperature is raised to 10-30°C, the stirring reaction is continued for 8-10 h, dichloromethane with a volume of 2-3 times the volume of acetic acid and deionized water with a volume of 2-3 times the volume of acetic acid are added, the mixture is uniformly mixed and allowed to stand for stratification, the organic phase is taken, and dried at 50-60°C under vacuum conditions for 8-10 h to obtain decafluorodiphenyl sulfone.

[0019] As an optimization, the preparation method of the pre-modified montmorillonite in step (4) is: nano-montmorillonite, copper nitrate and deionized water are mixed uniformly in a mass ratio of 1:(2-3):(80-100), stirred at 85-95°C and 300-500 r / min for 20-24 h, filtered, washed with deionized water for 3-5 times, and dried at 70-80°C under vacuum conditions for 10-12 h to obtain the pre-modified montmorillonite.

[0020] As an optimization, the preparation method of the silane hydrolyzate in step (4) is as follows: allyl triethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(20-30), the pH is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare a silane hydrolyzate.

[0021] As an optimization, the process parameters of the injection molding in step (5) are as follows: the barrel temperature of the injection molding machine is set to 270-280°C, the injection pressure is set to 80-90 MPa, the mold temperature is set to 150-160°C, and the holding time is set to 30-40 s.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] When preparing the high-impact polyphenylsulfone composite material, the present invention comprises the following steps: reacting 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid to obtain bismercaptoborate; reacting 3-mercapto-1-propylamine and 2-pyridine formaldehyde to obtain pyridine Schiff base ligand; reacting the pyridine Schiff base ligand with copper acetate to obtain pyridine Schiff base copper complex; oxidizing pentafluorodiphenyl sulfide with potassium permanganate to obtain decafluorodiphenyl sulfone; polycondensing 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenyl diphenol and 2,2'-diallyl bisphenol A to obtain functionalized polyphenylsulfone; reacting nano-montmorillonite with copper nitrate to obtain pre-modified montmorillonite; reacting the pre-modified montmorillonite with allyl triethoxysilane to obtain modified montmorillonite; and mixing the functionalized polyphenylsulfone, modified montmorillonite, bismercaptoborate and pyridine Schiff base copper complex and then performing injection molding to obtain the high-impact polyphenylsulfone composite material.

[0024] First, 3-mercapto-1,3-propanediol and 4-mercaptophenylboronic acid are reacted to obtain bis-mercaptoborate; bis-mercaptoborate contains two mercapto groups, which can react with the carbon-carbon double bond introduced on the side chain of the functionalized polyphenylsulfone, and can also react with the carbon-carbon double bond introduced on the modified montmorillonite to form a cross-linked network, inhibit the relative slip of the molecular chain, and give the high-impact polyphenylsulfone composite material excellent impact resistance; the borate bond on the bis-mercaptoborate is a reversible covalent bond, which can give the high-impact polyphenylsulfone composite material excellent self-healing properties; 3-mercapto-1-propylamine and 2-pyridine formaldehyde are reacted to obtain a pyridine Schiff base ligand; the pyridine Schiff base ligand The pyridine Schiff base copper complex is prepared by reaction with copper acetate; the pyridine Schiff base copper complex contains two thiol groups, and like bisthiol borate, it can react with the carbon-carbon double bond introduced on the side chain of functionalized polyphenylsulfone, and can also react with the carbon-carbon double bond introduced on the modified montmorillonite to form a cross-linked network, inhibit the relative slip of the molecular chain, and give the high-impact polyphenylsulfone composite material excellent impact resistance; copper ions can destroy the cell membrane structure, hinder the physiological metabolism and cell function of bacteria, interfere with the replication and transcription of DNA in bacterial cells, and give the high-impact polyphenylsulfone composite material excellent antibacterial properties, broadening the application of polyphenylsulfone in the fields of medical and daily necessities.

[0025] Secondly, pentafluorodiphenyl sulfide is oxidized with potassium permanganate to obtain decafluorodiphenyl sulfone; 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenylene glycol and 2,2'-diallyl bisphenol A are polycondensed to obtain functionalized polyphenylsulfone; fluorine atoms and carbon-carbon double bonds are introduced into the side chains of polyphenylsulfone. The presence of fluorine atoms reduces the surface tension of the composite material, making it difficult for water molecules to form hydrogen bonds and interact with the fluorine-containing surface, thereby reducing the adsorption of water molecules and giving the high-impact polyphenylsulfone composite material excellent hydrophobic properties; the carbon-carbon double bonds introduced into the side chains of polyphenylsulfone can react with the thiol groups on dithioborate and pyridine Schiff base copper complexes to form a cross-linked network, inhibiting the relative slip of the molecular chains and giving the high-impact polyphenylsulfone composite material excellent impact resistance.

[0026] Finally, the nano-montmorillonite is reacted with copper nitrate to obtain pre-modified montmorillonite. The cation exchange property of montmorillonite is used to load copper ions on the pre-modified montmorillonite. When the composite material is damaged, these copper ions can combine with the pyridine Schiff base ligands in the composite material to reform the coordination bonds, repair the composite material, and form a double self-repairing with the borate bond, further improving the self-repairing properties of the high impact resistant polyphenylsulfone composite material; the pre-modified montmorillonite is reacted with allyltriethoxysilane to obtain modified montmorillonite, and carbon-carbon double bonds are introduced into the modified montmorillonite. These carbon-carbon double bonds can also It reacts with the thiol groups on the dithioborate and pyridine Schiff base copper complexes to form a cross-linked network, inhibiting the relative slip of the molecular chains and giving the high-impact polyphenylsulfone composite material excellent impact resistance; Nano-montmorillonite has a one-dimensional layered nanostructure, which can effectively prevent the expansion of cracks and improve the fracture toughness of the material. The surface of the nano-montmorillonite is modified to enhance the compatibility of the nano-montmorillonite with the matrix resin, so that the nano-montmorillonite is evenly dispersed in the matrix resin, giving full play to the reinforcing and toughening functions of the nano-montmorillonite, and giving the high-impact polyphenylsulfone composite material excellent impact resistance. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A method for preparing a high-impact polyphenylsulfone composite material, the method for preparing the high-impact polyphenylsulfone composite material comprising the following preparation steps:

[0030] (1) 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid were added in a molar ratio of 1:1 to tetrahydrofuran (10 times the mass of 3-mercapto-1,3-propanediol), and anhydrous magnesium sulfate (0.03 times the mass of 3-mercapto-1,3-propanediol) was added, and the mixture was stirred at 40°C and 300 r / min for 8 hours, and dried at 50°C under vacuum for 10 hours to obtain bismercaptoborate;

[0031] (2) Add 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde in a molar ratio of 1:1 to methanol (10 times the mass of 3-mercapto-1-propylamine), stir and reflux at 65°C and 300 r / min for 3 hours, and dry at 50°C for 10 hours under vacuum conditions to obtain a pyridine Schiff base ligand; add copper acetate and pyridine Schiff base ligand in a molar ratio of 1:2 to methanol (10 times the mass of pyridine Schiff base ligand), stir and reflux at 65°C and 300 r / min for 3 hours, and dry at 50°C for 10 hours under vacuum conditions to obtain a pyridine Schiff base copper complex;

[0032] (3) Under nitrogen atmosphere, pentafluorodiphenyl sulfide, potassium permanganate and acetic acid were mixed in a mass ratio of 1:0.4:12, stirred at 10°C and 300 r / min for 14 min, and then added dropwise at a rate of 1.5 times the mass of pentafluorodiphenyl sulfide in a 98% aqueous sulfuric acid solution at 0°C and 300 r / min for 10 min. The temperature was raised to 10°C, and the stirring reaction was continued for 10 h. Dichloromethane (2 times the volume of acetic acid) and deionized water (2 times the volume of acetic acid) were added, the mixture was mixed evenly, and the mixture was allowed to stand for stratification. The organic phase was taken and dried at 50°C under vacuum for 10 h to obtain decafluorodiphenyl sulfone. 4,4' -Difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenyl diphenol, 2,2'-diallyl bisphenol A, and potassium carbonate were mixed in a molar ratio of 1:0.7:1:0.7:1.1, 10 times the mass of 4,4'-difluorodiphenyl sulfone and 5 times the mass of 4,4'-difluorodiphenyl sulfone of cyclopentane and toluene, stirred and refluxed at 140°C and 300r / min for 4h, heated to 185°C, continued to stir and react for 8h, cooled to room temperature, added deionized water twice the volume of cyclopentane, allowed to stand for 6h, filtered, washed 3 times with anhydrous ethanol and deionized water respectively, dried at 50°C for 10h under vacuum conditions to obtain functionalized polyphenylsulfone;

[0033] (4) Mix nano-montmorillonite, copper nitrate and deionized water in a mass ratio of 1:2:80, stir and react at 85°C and 300 r / min for 24 hours, filter, wash with deionized water three times, and dry at 70°C for 12 hours under vacuum to obtain pre-modified montmorillonite; mix allyl triethoxysilane and anhydrous ethanol in a mass ratio of 1:20, adjust the pH to 4 with 1 mol / L oxalic acid aqueous solution, stir at 10°C and 300 r / min for 60 minutes to prepare a silane hydrolyzate; mix pre-modified montmorillonite and anhydrous ethanol in a mass ratio of 1:50, add silane hydrolyzate 8 times the mass of pre-modified montmorillonite, stir and react at 50°C and 300 r / min for 3 hours, filter, wash with anhydrous ethanol three times, and dry at 50°C for 10 hours under vacuum to obtain modified montmorillonite;

[0034] (5) Functionalized polyphenylsulfone, modified montmorillonite, bis(thio)borate, and pyridine Schiff base copper complex were added into an injection molding machine at a mass ratio of 1:0.03:0.10:0.10. The barrel temperature of the injection molding machine was set to 270°C, the injection pressure was set to 80 MPa, the mold temperature was set to 150°C, and the holding time was set to 40 s. High impact resistant polyphenylsulfone composite materials were obtained by injection molding.

[0035] Example 2

[0036] A method for preparing a high-impact polyphenylsulfone composite material, the method for preparing the high-impact polyphenylsulfone composite material comprising the following preparation steps:

[0037] (1) 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid were added in a molar ratio of 1:1 to tetrahydrofuran (11 times the mass of 3-mercapto-1,3-propanediol), and anhydrous magnesium sulfate (0.04 times the mass of 3-mercapto-1,3-propanediol) was added, and the mixture was stirred at 45°C and 400 r / min for 7 hours, and dried at 55°C under vacuum for 9 hours to obtain bismercaptoborate;

[0038] (2) Add 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde in a molar ratio of 1:1 to methanol (11 times the mass of 3-mercapto-1-propylamine), stir and reflux at 70°C and 400 r / min for 2.5 hours, and dry at 55°C for 9 hours under vacuum conditions to obtain a pyridine Schiff base ligand; add copper acetate and pyridine Schiff base ligand in a molar ratio of 1:2 to methanol (11 times the mass of pyridine Schiff base ligand), stir and reflux at 70°C and 400 r / min for 2.5 hours, and dry at 55°C for 9 hours under vacuum conditions to obtain a pyridine Schiff base copper complex;

[0039] (3) Under nitrogen atmosphere, pentafluorodiphenyl sulfide, potassium permanganate and acetic acid were mixed in a mass ratio of 1:0.5:13, stirred at 20°C and 400 r / min for 12 min, and then added dropwise at a rate of 1.55 times the mass of pentafluorodiphenyl sulfide in a 98% aqueous sulfuric acid solution at 1°C and 400 r / min for 10 min. The temperature was raised to 20°C and the stirring reaction was continued for 9 h. Dichloromethane (2.5 times the volume of acetic acid) and deionized water (2.5 times the volume of acetic acid) were added, the mixture was mixed evenly and allowed to stand for stratification. The organic phase was taken and dried at 55°C under vacuum for 9 h to obtain decafluorodiphenyl sulfone. Fluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenyl diphenol, 2,2'-diallyl bisphenol A, and potassium carbonate were mixed in a molar ratio of 1:0.8:1:0.8:1.15, and cyclopentane sulfone (11 times the mass of 4,4'-difluorodiphenyl sulfone) and toluene (5.5 times the mass of 4,4'-difluorodiphenyl sulfone) were added, and the mixture was stirred and refluxed at 145°C and 400 r / min for 3.5 hours, and the mixture was heated to 190°C and stirred for 7.5 hours. The mixture was cooled to room temperature, and deionized water (2.5 times the volume of cyclopentane sulfone) was added, and the mixture was allowed to stand for 7 hours. The mixture was filtered, and washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 55°C for 9 hours under vacuum conditions to obtain functionalized polyphenyl sulfone.

[0040] (4) Nano-montmorillonite, copper nitrate and deionized water were mixed in a mass ratio of 1:2.5:90, stirred at 90°C and 400 r / min for 22 h, filtered, washed with deionized water 4 times, and dried at 75°C for 11 h under vacuum to obtain pre-modified montmorillonite; allyl triethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:25, the pH was adjusted to 4.5 with 1 mol / L oxalic acid aqueous solution, stirred at 20°C and 400 r / min for 55 min to prepare a silane hydrolyzate; pre-modified montmorillonite and anhydrous ethanol were mixed in a mass ratio of 1:55, silane hydrolyzate of 9 times the mass of pre-modified montmorillonite was added, stirred at 55°C and 400 r / min for 2.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 55°C for 9 h under vacuum to obtain modified montmorillonite;

[0041] (5) Functionalized polyphenylsulfone, modified montmorillonite, bis(thio)borate, and pyridine Schiff base copper complex were added into an injection molding machine at a mass ratio of 1:0.04:0.11:0.11. The barrel temperature of the injection molding machine was set to 275°C, the injection pressure was set to 85 MPa, the mold temperature was set to 155°C, and the holding time was set to 35 s. High impact resistant polyphenylsulfone composite materials were obtained by injection molding.

[0042] Example 3

[0043] A method for preparing a high-impact polyphenylsulfone composite material, the method for preparing the high-impact polyphenylsulfone composite material comprising the following preparation steps:

[0044] (1) 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid were added in a molar ratio of 1:1 to tetrahydrofuran (12 times the mass of 3-mercapto-1,3-propanediol), and anhydrous magnesium sulfate (0.05 times the mass of 3-mercapto-1,3-propanediol) was added, and the mixture was stirred at 50°C and 500 r / min for 6 hours, and dried at 60°C under vacuum conditions for 8 hours to obtain bismercaptoborate;

[0045] (2) Add 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde in a molar ratio of 1:1 to methanol (12 times the mass of 3-mercapto-1-propylamine), stir and reflux at 75°C and 500 r / min for 2 hours, and dry at 60°C for 8 hours under vacuum conditions to obtain a pyridine Schiff base ligand; add copper acetate and pyridine Schiff base ligand in a molar ratio of 1:2 to methanol (12 times the mass of pyridine Schiff base ligand), stir and reflux at 75°C and 500 r / min for 2 hours, and dry at 60°C for 8 hours under vacuum conditions to obtain a pyridine Schiff base copper complex;

[0046] (3) Under nitrogen atmosphere, pentafluorodiphenyl sulfide, potassium permanganate and acetic acid were mixed in a mass ratio of 1:0.6:14, stirred at 30°C and 500 r / min for 10 min, and then added dropwise at a rate of 1.6 times the mass of pentafluorodiphenyl sulfide in a 98% aqueous sulfuric acid solution at 2°C and 500 r / min for 10 min. The temperature was raised to 30°C and the stirring reaction was continued for 8 h. Dichloromethane (3 times the volume of acetic acid) and deionized water (3 times the volume of acetic acid) were added, the mixture was mixed evenly and allowed to stand for stratification. The organic phase was taken and dried at 60°C under vacuum for 8 h to obtain decafluorodiphenyl sulfone. 4,4' -Difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenyl diphenol, 2,2'-diallyl bisphenol A, potassium carbonate were mixed in a molar ratio of 1:0.9:1:0.9:1.2, 12 times the mass of cyclopentane sulfone and 6 times the mass of 4,4'-difluorodiphenyl sulfone of toluene were added, stirred and refluxed at 150°C and 500r / min for 3h, heated to 195°C, continued to stir and react for 7h, cooled to room temperature, added deionized water 3 times the volume of cyclopentane sulfone, stood for 8h, filtered, washed 5 times with anhydrous ethanol and deionized water respectively, dried at 60°C under vacuum conditions for 8h to obtain functionalized polyphenylsulfone;

[0047] (4) Nano-montmorillonite, copper nitrate and deionized water were mixed in a mass ratio of 1:3:100, stirred at 95°C and 500 r / min for 20 h, filtered, washed with deionized water 5 times, and dried at 80°C for 10 h under vacuum to obtain pre-modified montmorillonite; allyl triethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:30, the pH was adjusted to 6 with 1 mol / L oxalic acid aqueous solution, stirred at 30°C and 500 r / min for 50 min to prepare a silane hydrolyzate; pre-modified montmorillonite and anhydrous ethanol were mixed in a mass ratio of 1:60, 10 times the mass of the pre-modified montmorillonite was added with the silane hydrolyzate, stirred at 60°C and 500 r / min for 2 h, filtered, washed with anhydrous ethanol 5 times, and dried at 60°C for 8 h under vacuum to obtain modified montmorillonite;

[0048] (5) Functionalized polyphenylsulfone, modified montmorillonite, bis(thio)borate, and pyridine Schiff base copper complex were added into an injection molding machine at a mass ratio of 1:0.05:0.12:0.12. The barrel temperature of the injection molding machine was set to 280°C, the injection pressure was set to 90 MPa, the mold temperature was set to 160°C, and the holding time was set to 30 s. High impact resistant polyphenylsulfone composite materials were obtained by injection molding.

[0049] Comparative Example 1

[0050] The preparation method of the high impact resistant polyphenylsulfone composite material of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (5) is modified as follows: functionalized polyphenylsulfone, modified montmorillonite, and pyridine Schiff base copper complex are added to an injection molding machine at a mass ratio of 1:0.04:0.11, the barrel temperature of the injection molding machine is set to 275° C., the injection pressure is set to 85 MPa, the mold temperature is set to 155° C., the holding time is set to 35 s, and the high impact resistant polyphenylsulfone composite material is obtained by injection molding. The remaining steps are the same as those of Example 2.

[0051] Comparative Example 2

[0052] The preparation method of the high impact resistant polyphenylsulfone composite material of Comparative Example 2 is different from that of Example 2 in that step (2) is not performed, and step (5) is modified as follows: functionalized polyphenylsulfone, modified montmorillonite, and bisthioboric acid ester are added into an injection molding machine at a mass ratio of 1:0.04:0.11, the barrel temperature of the injection molding machine is set to 275°C, the injection pressure is set to 85 MPa, the mold temperature is set to 155°C, the holding time is set to 35 s, and the high impact resistant polyphenylsulfone composite material is obtained by injection molding. The remaining steps are the same as those of Example 2.

[0053] Comparative Example 3

[0054] The preparation method of the high impact resistant polyphenylsulfone composite material of comparative example 3 is different from that of example 2 only in step (3), and step (3) is modified as follows: 4,4'-difluorodiphenyl sulfone, biphenyl diphenol, 2,2'-diallyl bisphenol A, and potassium carbonate are mixed uniformly in a molar ratio of 1.8:1:0.8:1.15, 11 times the mass of cyclopentane and 5.5 times the mass of 4,4'-difluorodiphenyl sulfone are added, and the mixture is stirred and refluxed at 145°C and 400 r / min for 3.5 hours, the mixture is heated to 190°C, the reaction is continued under stirring for 7.5 hours, the mixture is cooled to room temperature, 2.5 times the volume of cyclopentane deionized water is added, the mixture is allowed to stand for 7 hours, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 55°C under vacuum for 9 hours to obtain functionalized polyphenylsulfone. The remaining steps are the same as those of example 2.

[0055] Comparative Example 4

[0056] The preparation method of the high impact resistant polyphenylsulfone composite material of Comparative Example 4 is different from that of Example 2 only in step (3). Step (3) is modified as follows: under a nitrogen atmosphere, pentafluorodiphenyl sulfide, potassium permanganate and acetic acid are mixed uniformly in a mass ratio of 1:0.5:13, stirred at 20°C and 400 r / min for 12 min, and under stirring conditions of 1°C and 400 r / min, a 98% aqueous sulfuric acid solution with a mass fraction of 1.55 times the mass of pentafluorodiphenyl sulfide is added dropwise at a uniform rate within 10 min, the temperature is raised to 20°C, and the stirring reaction is continued for 9 h, dichloromethane with a volume of 2.5 times the volume of acetic acid and deionized water with a volume of 2.5 times the volume of acetic acid are added, the mixture is mixed uniformly and allowed to stand for stratification, and the organic phase is taken. , under vacuum conditions, dried at 55°C for 9h to obtain decafluorodiphenyl sulfone; 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenyl diphenol, and potassium carbonate were mixed uniformly at a molar ratio of 1:0.8:1.8:1.15, 11 times the mass of 4,4'-difluorodiphenyl sulfone and 5.5 times the mass of 4,4'-difluorodiphenyl sulfone were added, stirred and refluxed at 145°C and 400r / min for 3.5h, heated to 190°C, continued to stir and react for 7.5h, cooled to room temperature, added 2.5 times the volume of sulfone deionized water, stood for 7h, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 55°C for 9h under vacuum conditions to obtain functionalized polyphenyl sulfone. The remaining steps are the same as those in Example 2.

[0057] Comparative Example 5

[0058] The preparation method of the high impact resistant polyphenylsulfone composite material of Comparative Example 5 is different from that of Example 2 in that step (4) is not performed, and step (5) is modified as follows: functionalized polyphenylsulfone, nano-montmorillonite, bisthioborate, and pyridine Schiff base copper complex are added to an injection molding machine in a mass ratio of 1:0.04:0.11:0.11, the barrel temperature of the injection molding machine is set to 275°C, the injection pressure is set to 85 MPa, the mold temperature is set to 155°C, the holding time is set to 35 s, and the high impact resistant polyphenylsulfone composite material is obtained by injection molding.

[0059] Test Example 1

[0060] Antimicrobial performance testing

[0061] Test method: The examples and comparative examples were cut into 10 mm × 10 mm samples and sterilized by ultraviolet irradiation for 3 h; the Escherichia coli strains were activated and prepared to a concentration of 3 × 10 4 cfu / ml bacterial suspension; put the sample into the bacterial suspension, shake at 300r / min for 5min at room temperature, take 1ml of the bacterial suspension and dilute it to 100 times, take 1ml of the diluted bacterial suspension and inoculate it into agar medium, culture it at 37℃ for 16h, count the colonies according to the method in GB / T15979, and calculate the antibacterial rate. The results are shown in Table 1.

[0062] Table 1

[0063] Antibacterial rate (%) Antibacterial rate (%) Example 1 99.76 Comparative Example 1 99.63 Example 2 99.81 Comparative Example 2 73.24 Example 3 99.79 Comparative Example 3 99.65 Comparative Example 4 99.59 Comparative Example 5 86.13

[0064] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the high impact-resistant polyphenylsulfone composite material prepared in the present invention has good antibacterial properties.

[0065] By comparison, the antibacterial rates of Examples 1 to 3 are greater than those of Comparative Examples 2 and 5, indicating that 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde are reacted to obtain a pyridine Schiff base ligand; the pyridine Schiff base ligand is reacted with copper acetate to obtain a pyridine Schiff base copper complex; nano-montmorillonite is reacted with copper nitrate to obtain a pre-modified montmorillonite, and copper ions are loaded on the pre-modified montmorillonite by utilizing the cation exchange property of montmorillonite; copper ions can destroy the cell membrane structure, hinder the physiological metabolism and cell function of bacteria, interfere with the replication and transcription of DNA in bacterial cells, and impart excellent antibacterial properties to the high-impact polyphenylsulfone composite material.

[0066] Test Example 2

[0067] Hydrophobicity test

[0068] Test method: The water drop contact angles of the embodiments and comparative examples were tested using the sessile drop method on an OCA20 contact angle meter, with the water drop volume being 5 μL. The results are shown in Table 2.

[0069] Table 2

[0070] Contact angle Contact angle Example 1 121.56° Comparative Example 1 120.68° Example 2 124.21° Comparative Example 2 121.03° Example 3 122.85° Comparative Example 3 84.71° Comparative Example 4 119.54° Comparative Example 5 120.39°

[0071] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the high impact resistant polyphenylsulfone composite material prepared in the present invention has good hydrophobic properties.

[0072] By comparison, the contact angles of Examples 1 to 3 are greater than the contact angle of Comparative Example 3, indicating that decafluorodiphenyl sulfone is prepared by oxidizing pentafluorodiphenyl sulfide with potassium permanganate; functionalized polyphenylsulfone is prepared by polycondensation of 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenylene glycol, and 2,2'-diallyl bisphenol A; fluorine atoms are introduced into the side chains of polyphenylsulfone. The presence of fluorine atoms reduces the surface tension of the composite material, making it difficult for water molecules to form hydrogen bonds and interact with the fluorine-containing surface, thereby reducing the adsorption of water molecules and giving the high-impact polyphenylsulfone composite material excellent hydrophobic properties.

[0073] Test Example 3

[0074] Impact resistance test

[0075] Test method: The impact strength of the examples and comparative examples was tested on an impact tester according to GB / T1843. The results are shown in Table 3.

[0076] Table 3

[0077] <![CDATA[Impact strength (kJ / m 2 )]]> <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 92.58 Comparative Example 1 71.64 Example 2 93.42 Comparative Example 2 68.33 Example 3 91.85 Comparative Example 3 91.02 Comparative Example 4 65.91 Comparative Example 5 72.13

[0078] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 3, it can be found that the high impact-resistant polyphenylsulfone composite material prepared in the present invention has good impact resistance.

[0079] By comparison, the impact strength of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that bis-mercaptoborate is prepared by reacting 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid; bis-mercaptoborate contains two mercapto groups, which can react with the carbon-carbon double bond introduced on the side chain of the functionalized polyphenylsulfone, and can also react with the carbon-carbon double bond introduced on the modified montmorillonite to form a cross-linked network, inhibit the relative slip of the molecular chains, and impart excellent impact resistance to the high-impact polyphenylsulfone composite material.

[0080] By comparison, the impact strength of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde are reacted to obtain a pyridine Schiff base ligand; the pyridine Schiff base ligand is reacted with copper acetate to obtain a pyridine Schiff base copper complex; the pyridine Schiff base copper complex contains two mercapto groups, which, like bismercaptoborate, can react with the carbon-carbon double bond introduced on the side chain of the functionalized polyphenylsulfone, and can also react with the carbon-carbon double bond introduced on the modified montmorillonite to form a cross-linked network, inhibit the relative slip of the molecular chains, and impart excellent impact resistance to the high-impact polyphenylsulfone composite material.

[0081] By comparison, the impact strength of Examples 1 to 3 is greater than that of Comparative Example 4, indicating that the functionalized polyphenylsulfone is prepared by polycondensation of 4,4'-difluorodiphenylsulfone, decafluorodiphenylsulfone, biphenylene glycol, and 2,2'-diallylbisphenol A; a carbon-carbon double bond is introduced into the side chain of the polyphenylsulfone, and the carbon-carbon double bond introduced into the side chain of the polyphenylsulfone can react with the thiol groups on the bisthioborate and pyridine Schiff base copper complex to form a cross-linked network, thereby inhibiting the relative slip of the molecular chains and giving the high-impact polyphenylsulfone composite material excellent impact resistance.

[0082] By comparison, the impact strength of Examples 1 to 3 is greater than the impact strength of Comparative Example 5, indicating that the modified montmorillonite is prepared by reacting the pre-modified montmorillonite with allyltriethoxysilane, and carbon-carbon double bonds are introduced into the modified montmorillonite. These carbon-carbon double bonds can also react with the thiol groups on the bisthioborate and pyridine Schiff base copper complexes to form a cross-linked network, inhibit the relative slip of the molecular chains, and give the high-impact polyphenylsulfone composite material excellent impact resistance; the nano-montmorillonite has a one-dimensional layered nanostructure, which can effectively prevent the expansion of cracks and improve the fracture toughness of the material. The surface of the nano-montmorillonite is modified to enhance the compatibility of the nano-montmorillonite with the matrix resin, so that the nano-montmorillonite is evenly dispersed in the matrix resin, and the reinforcing and toughening functions of the nano-montmorillonite are fully exerted, giving the high-impact polyphenylsulfone composite material excellent impact resistance.

[0083] Test Example 4

[0084] Self-healing performance test

[0085] Test method: According to GB / T1040.1, the embodiment and the comparative example were cut into standard strips, and their original tensile strength was tested with a tensile machine. Then, a 5mm deep and 20mm long crack was cut from the middle of the unstretched strip, and the strip was kept at 60°C for 4 hours and allowed to stand at room temperature for 10 hours to obtain the repaired strip. The tensile strength was tested with a tensile machine. The self-repair rate of the embodiment and the comparative example before and after repair was calculated, and the self-repair rate = (tensile strength of the repaired strip / original tensile strength of the strip) × 100%. The results are shown in Table 4.

[0086] Table 4

[0087] Self-repair rate (%) Self-repair rate (%) Example 1 95.78 Comparative Example 1 81.92 Example 2 96.22 Comparative Example 2 85.19 Example 3 95.95 Comparative Example 3 94.96 Comparative Example 4 95.07 Comparative Example 5 82.71

[0088] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 4, it can be found that the high impact resistant polyphenylsulfone composite material prepared in the present invention has good self-repairing performance.

[0089] By comparison, the self-repair rates of Examples 1 to 3 are greater than that of Comparative Example 1, indicating that bis-mercaptoborate is prepared by reacting 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid; the borate bond on the bis-mercaptoborate is a reversible covalent bond, which gives the high-impact polyphenylsulfone composite material excellent self-repairing properties.

[0090] By comparison, the self-repairing rates of Examples 1 to 3 are greater than those of Comparative Examples 2 and 5, indicating that 3-mercapto-1-propylamine and 2-pyridinecarboxaldehyde are reacted to obtain pyridine Schiff base ligands; nano-montmorillonite is reacted with copper nitrate to obtain pre-modified montmorillonite, and copper ions are loaded on the pre-modified montmorillonite by utilizing the cation exchange property of montmorillonite. When the composite material is damaged, these copper ions can combine with the pyridine Schiff base ligands in the composite material to reform coordination bonds, thereby repairing the composite material and forming double self-repairing with the borate bond, thereby further improving the self-repairing performance of the high impact-resistant polyphenylsulfone composite material.

[0091] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high impact resistant polyphenylsulfone composite material, characterized in that: The method comprises the following preparation steps: (1) Add 3-mercapto-1,3-propanediol and 4-mercaptophenylboric acid in a molar ratio of 1:1 to tetrahydrofuran (10 to 12 times the mass of 3-mercapto-1,3-propanediol), add anhydrous magnesium sulfate (0.03 to 0.05 times the mass of 3-mercapto-1,3-propanediol), stir at 40 to 50°C and 300 to 500 r / min for 6 to 8 hours, and dry at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain bismercaptoborate; (2) adding copper acetate and pyridine Schiff base ligand in a molar ratio of 1:2 to methanol with a mass 10 to 12 times that of the pyridine Schiff base ligand, stirring and refluxing at 65 to 75°C and 300 to 500 r / min for 2 to 3 hours, and drying at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain a pyridine Schiff base copper complex; (3) 4,4'-difluorodiphenyl sulfone, decafluorodiphenyl sulfone, biphenylene, 2,2'-diallyl bisphenol A and potassium carbonate were mixed in a molar ratio of 1:(0.7~0.9):1:(0.7~0.9):(1.1~1.2), 10~12 times the mass of cyclopentane sulfone and 5~6 times the mass of toluene 4,4'-difluorodiphenyl sulfone were added, and the mixture was stirred and refluxed at 140~150°C and 300~500r / min for 3~4h, heated to 185~195°C, and stirred for 7~8h. The mixture was cooled to room temperature, and deionized water 2~3 times the volume of cyclopentane sulfone was added. The mixture was allowed to stand for 6~8h, filtered, washed with anhydrous ethanol and deionized water for 3~5 times respectively, and dried at 50~60°C under vacuum for 8~10h to obtain functionalized polyphenylsulfone; (4) Pre-modified montmorillonite and anhydrous ethanol were mixed evenly in a mass ratio of 1:(50-60), silane hydrolyzate in an amount of 8-10 times the mass of the pre-modified montmorillonite was added, and the mixture was stirred at 50-60°C and 300-500 r / min for 2-3 h, filtered, washed with anhydrous ethanol for 3-5 times, and dried at 50-60°C under vacuum for 8-10 h to obtain modified montmorillonite; (5) adding functionalized polyphenylsulfone, modified montmorillonite, bisthioborate, and pyridine Schiff base copper complex into an injection molding machine at a mass ratio of 1:(0.03-0.05):(0.10-0.12):(0.10-0.12), and performing injection molding to obtain a high impact resistant polyphenylsulfone composite material; The preparation method of the pyridine Schiff base ligand in step (2) is as follows: 3-mercapto-1-propylamine and 2-pyridine formaldehyde are added in a molar ratio of 1:1 to methanol with a mass that is 10 to 12 times that of 3-mercapto-1-propylamine, and the mixture is stirred and refluxed at 65 to 75°C and 300 to 500 r / min for 2 to 3 hours, and dried at 50 to 60°C under vacuum conditions for 8 to 10 hours to obtain the pyridine Schiff base ligand; The preparation method of the pre-modified montmorillonite in step (4) is as follows: nano-montmorillonite, copper nitrate and deionized water are uniformly mixed in a mass ratio of 1:(2-3):(80-100), stirred at 85-95°C and 300-500 r / min for 20-24 h, filtered, washed with deionized water for 3-5 times, and dried at 70-80°C under vacuum for 10-12 h to obtain the pre-modified montmorillonite; The preparation method of the silane hydrolyzate in step (4) is as follows: allyl triethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(20-30), the pH is adjusted to 4-6 with a 1 mol / L oxalic acid aqueous solution, and the mixture is stirred at 10-30° C. and 300-500 r / min for 50-60 min to prepare a silane hydrolyzate.

2. The method for preparing a high impact resistant polyphenylsulfone composite material according to claim 1, characterized in that: The reaction process of the pyridine Schiff base copper complex in step (2) is: 。 3. The method for preparing a high impact resistant polyphenylsulfone composite material according to claim 1, characterized in that: The preparation method of the decafluorodiphenyl sulfone in step (3) is as follows: under a nitrogen atmosphere, pentafluorodiphenyl sulfide, potassium permanganate and acetic acid are uniformly mixed in a mass ratio of 1:(0.4-0.6):(12-14), stirred at 10-30° C. and 300-500 r / min for 10-14 min, and at 0-2° C. and 300-500 r / min, a 98% aqueous sulfuric acid solution with a mass fraction of 1.5-1.6 times the mass of pentafluorodiphenyl sulfide is added dropwise at a uniform rate within 10 min, the temperature is raised to 10-30° C., the stirring reaction is continued for 8-10 h, dichloromethane with a volume of 2-3 times the volume of acetic acid and deionized water with a volume of 2-3 times the volume of acetic acid are added, the mixture is uniformly mixed and allowed to stand for stratification, the organic phase is taken, and dried at 50-60° C. under vacuum conditions for 8-10 h to obtain decafluorodiphenyl sulfone.

4. The method for preparing a high impact resistant polyphenylsulfone composite material according to claim 1, characterized in that: The process parameters of the injection molding in step (5) are as follows: the barrel temperature of the injection molding machine is set to 270-280°C, the injection pressure is set to 80-90 MPa, the mold temperature is set to 150-160°C, and the holding time is set to 30-40 s.

5. A high-impact polyphenylsulfone composite material prepared according to the method for preparing a high-impact polyphenylsulfone composite material according to any one of claims 1 to 4.

Citation Information

Cited By

  • Polysulfone with ultra-narrow molecular weight distribution and high yield and preparation method thereof

    CN120173241A